Hazard Assessment of Soil Contamination resulting from Solid Waste Trench Landfill Systems - Rodrigues, Grasiele Simplicio Murari; Kaiser, Ilza Machado; Peixoto, Anna Silvia Palcheco (National Journal of City Management, 2023)
Contamination due to the inadequate disposal of solid waste can cause irreversible environmental damage and public health risks. In the state of São Paulo (Brazil), legislation allows small municipalities to license landfills adopting the trench model. In most cases, it is not mandatory to carry out environmental protection works such as waterproof lining and the drainage of leachate and gases. The aim of this research was to evaluate soil contamination hazards resulting from Solid Waste Trench Landfill Systems (SWTLS). An consultation with experts was carried out in which a Hazard Level (HL) score was applied that considered factors such as geology, pedology, geomorphology, hydrography, groundwater, environmental protection, land use, composition and gravimetric demographic densities. A resource management unit, UGRHI 16 - Tietê Batalha Hydrographic Basin, was defined as the study area, where hazard level was identified to the trench landfill. It was also found that all the municipalities studied are exempt from installing linings in their landfills, in accordance with Brazilian standards, as water surpluses, analyzed in terms of local rainfall, comply with the limits established by regulation. However, the evaluation carried out as part of the present research considered other important factors, through which the existence of risks at different levels for all the municipalities evaluated in relation to the adoption of small SWTLS was noted. The study concluded that the factors adopted for the research are relevant to decision making in terms of system design and the definition of criteria regarding the need for protective lining.